2021
DOI: 10.15252/embr.202152679
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of microtubule‐destabilizing factors during dendrite pruning in Drosophila

Abstract: It has long been thought that microtubule disassembly, one of the earliest cellular events, contributes to neuronal pruning and neurodegeneration in development and disease. However, how microtubule disassembly drives neuronal pruning remains poorly understood. Here, we conduct a systematic investigation of various microtubule-destabilizing factors and identify exchange factor for Arf6 (Efa6) and Stathmin (Stai) as new regulators of dendrite pruning in ddaC sensory neurons during Drosophila metamorphosis. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 91 publications
1
12
0
Order By: Relevance
“…Thus, these data suggest that both reduction and overexpression of Orbit enhance microtubule turnover in dendrites. A previous study has reported that higher microtubule turnover can accelerate the dendrite pruning process in ddaC neurons, leading to precocious dendrite pruning at 7 h APF (Bu et al, 2021). Unexpectedly, our present data indicate that both loss and gain of orbit functions did not lead to precocious dendrite pruning but rather caused the dendrite pruning defects in ddaC neurons (Figures 1 and S2).…”
Section: Overexpression Of Orbit Inhibits Dendrite Pruningsupporting
confidence: 61%
See 2 more Smart Citations
“…Thus, these data suggest that both reduction and overexpression of Orbit enhance microtubule turnover in dendrites. A previous study has reported that higher microtubule turnover can accelerate the dendrite pruning process in ddaC neurons, leading to precocious dendrite pruning at 7 h APF (Bu et al, 2021). Unexpectedly, our present data indicate that both loss and gain of orbit functions did not lead to precocious dendrite pruning but rather caused the dendrite pruning defects in ddaC neurons (Figures 1 and S2).…”
Section: Overexpression Of Orbit Inhibits Dendrite Pruningsupporting
confidence: 61%
“…These data indicate that Orbit can stabilize dendritic microtubules in postmitotic ddaC neurons. To test whether Orbit is important for microtubule turnover in the dendrites, we conducted the photoconversion assays by expressing a photoconvertible tdEOS:a-tubulin (Barlan et al, 2013;Bu et al, 2021;Herzmann et al, 2017;Lu et al, 2013;Tao et al, 2016). Because mature neurons lose the ability of microtubule sliding (Lu et al, 2013(Lu et al, , 2015, the photoconversion assays can be used to measure microtubule turnover or disassembly in ddaC neurons from the third instar larval stage (Tao et al, 2016).…”
Section: Overexpression Of Orbit Inhibits Dendrite Pruningmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been thought that localized breakage of MTs is one of the earliest cellular events, contributes to neuronal pruning ( Bu et al, 2021 ; Lee et al, 2009 ; Williams and Truman, 2005 ). In order to visualize the MTs, we drove tubulin-GFP by OK6-Gal4 to specifically label the MTs in motor neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies have suggested that ecdysone signaling is the main gatekeeper of axon/dendrite remodeling ( Kirilly et al, 2009 , 2011 ; Lee et al, 2000 ; Zheng et al, 2003 ). Furthermore, several known pathways that contribute to neurite pruning have been revealed: ubiquitin proteasomal degradation ( Kuo et al, 2005 ; Watts et al, 2003 ; Wong et al, 2013 ), caspase activity ( Kuo et al, 2006 ; Williams et al, 2006 ), microtubule disassembly ( Bu et al, 2021 ; Herzmann et al, 2017 ; Lee et al, 2009 ) and polarity ( Herzmann et al, 2018 ; Rui et al, 2020b ; Tang et al, 2020 ; Wang et al, 2019 ), glia engulf ( Awasaki et al, 2011 ; Awasaki and Ito, 2004 ; Tasdemir-Yilmaz and Freeman, 2014 ; Watts et al, 2004 ), epithelial engulf ( Han et al, 2014 ), nitric oxide ( Rabinovich et al, 2016 ), secretory pathway ( Rui et al, 2020a ; Wang et al, 2017 ), endocytic pathway ( Issman-Zecharya and Schuldiner, 2014 ; Zhang et al, 2014 ), cell adhesion ( Bornstein et al, 2015 ) and energy metabolism ( Marzano et al, 2021 ). Importantly, during the past few decades, developmental neuronal pruning has been reported in various mammalian brain regions, including the hippocampus, cortex, cerebellum, and olfactory bulb ( Luo and O'Leary, 2005 ; Riccomagno and Kolodkin, 2015 ; Schuldiner and Yaron, 2015 ).…”
Section: Introductionmentioning
confidence: 99%